ANALISIS KEPUASAN KONSUMEN DENGAN MENGGUNAKAN METODE HOMBSAT PADA PERUNAHAN PELEM SEWU BARU - Sirunyoto, Sirunyoto; Fajarwati, Fajarwati (Universitas Muhammadiyah Magelang, 2006)
Improving customer satisfaction has been identified as one of most important challenges facing business. Keeping customers satisfied is rapidly becoming the way companies differentiate themselves from competitors. This research describes the development of a 51-item instrument, called HOMBSAT, for assesing home buyer satisfaction. A model was proposed describing home-buyer satisfaction as a three-dimensional composite of satisfaction with design, house and service. That instrument was found to be both valid and reliable. From the analysis of research all variable is different of satisfied and house is dominant variable.